Vital Concerns and Vital Illusions - Code, Murray (Cosmos and History: The Journal of Natural and Social Philosophy, 2012)
A consumer society that has embraced global capitalism while striving to preserve all the comforts and conveniences provided by technoscience is arguably fatally ill. Much support for this gloomy diagnosis is provided by, among others, Hannah Arendt, Northrop Frye, and Friedrich Nietzsche. Their reflections on the health of a human culture point up the urgency of the need to rethink the idea of good reasoning that predominates in the West. However, they also indicate that a healthier, more life-enhancing conception of good reasoning will arise only when a concern for justice and wisdom displaces the traditional ideals of pure and certain knowledge or eternal truths. To this end, Nietzsche recommends that philosophy ought now to concentrate on producing `cultural physicians’ who would strive to fashion a philosophy of concern. This type of philosophical therapist requires a radically nonmodern approach to philosophy that must pivot on a vitalistic metaphysics capable of overcoming pervasive nihilistic ideologies which illustrate a globally spreading mythology of unconcern. Hence an effective and lasting cultural therapy will depend on the emergence of a general will/desire to broaden the conception of good reasoning beyond the narrow perspectives established by modern science. And this will depend in turn on the education of future educators who stress above all the importance of cultivating the mythopoeic imaginations of the young.